The importance of job training as a catalyst for change in organizational performance - Ramírez Cabrejo, Hollman Badwan (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Job training or training processes carried out within organizations have become a fundamental factor for the operation of companies, this is due to their influence on human capital and their direct relationship with the development of processes. This article, developed through a review research process, exposes from various perspectives the impact of job training on organizational performance, in terms of productivity, job satisfaction, and talent retention. Additionally, it allows visualizing the different models and types of existing training processes, which provide training alternatives and the ability to adapt them to any organization.